Leading in the NHS : a practical guide - Stewart, Rosemary (Basingstoke : Macmillan, 1996)
This text is aimed at those who hold, or intend to hold, a responsible job within the National Health Service. Its aim is to persuade the reader that there is a need for leadership within the NHS and then to make the reader think about what he or she wants to achieve.
Guide to Reading This Book - Glossary of Acronyms - Introduction to First Edition - Introduction to Second Edition - PART 1: THE CONCEPT OF LEADERSHIP - Leadership - PART 2: LEADING IN DIFFERENT RELATIONSHIPS - Leading Staff - Leadership and Nurses - Leadership and Doctors - Sharing the Leadership: Chair and Chief Executive - Sharing the Leadership: Team Working - Leadership and The Board - Leading in The Regional Office - External Leadership - PART 3: LEADERSHIP IN ACTION - Four Young Leaders - Clinical Leaders - The Twin Aspects of Leadership: A Case Study - PART 4: DEVELOPING YOURSELF - Managing The Job and Yourself - Developing Yourself - In Conclusion - Appendix A: Details of the Templeton Tracer Study of DGMs - Appendix B: Questions Asked Young Leaders
Previous ed.: 1989.
Includes index.
Keywords: Health services administration -- Great Britain